Transabdominal Vs Transvaginal Sonography - Comparison in Pelvic Pathologies - Manal Niazi,Mahjabeen Mahmood Kamal,Naushaba Malik,Muhammad Ashraf Farooq ,Neelum Wahid (Journal of Rawalpindi Medical College, 2015)
Background: To compare and find diagnostic accuracy and efficacy of trans-vaginal and trans-abdominal sonographic techniques in female pelvic pathologies and to compare both the procedures against the gold standard of biopsy. Methods: In this comparative study two hundred patients with clinical evidence of pelvic disease of gynaecologic origin and patients with suspected ectopic pregnancy already planned to undergo surgery and/or biopsy were included. Trans-abdominal ultrasounds and trans-vaginal ultrasounds were performed by different radiologists. Uterus, adnexa and ovaries were viewed in sagittal, transverse and oblique views. The endovaginal transducer was sheathed in a condom into which a small amount of ultrasound gel had been placed. Biopsy being the gold standard was done on all the patients. The information provided by TAS, TVS and biopsy was categorized as: (+)Disease Positive and (-)Disease Negative. Sensitivity, specificity and predictive value of both the tests were calculated. Chi-square test was used to compare sensitivity of TVS and TAS. Student t-test was used to compare the difference between TAS and TVS for size of pelvic masses. Results: Trans-vaginal sonography (TVS) had sensitivity of 96%, specificity of 89%, positive predictive value of 97%, negative predictive value of 84%. Trans-abdominal sonography (TAS) had sensitivity of 91%, specificity of 83%, positive predictive value of 96%, negative predictive value of 68%. The comparison between the two tests was statistically significant (p<0.05). On the basis of image quality TVS was superior in 62%, equal in 30% and inferior in 08% of cases as compared to TAS. Conclusion: Trans-vaginal sonography is more sensitive and specific than trans-abdominal sonography.